BIOLOGICAL NITROGEN FIXATION, SOURCES AND LEVELS OF N INCREASE THE MAIZE GRAIN YIELD IN CERRADO - KANEKO, FLAVIO HIROSHI; FERREIRA, JOÃO PAULO; SABUNDJIAN, MICHELLE TRAETE; FREITAS LEAL, AGUINALDO JOSÉ; VAN CLEEF, ERIC HAYDT CASTELLO BRANCO; REIS, ANDRÉ RODRIGUES; BUZETTI, SALATIÉR; ARF, MARCELO VALENTINI; ARF, ORIVALDO (International Journal of Maize & Sorghum, 2019)
The objective of this study was to evaluate the effects of inoculation with A. brasilense, sources and levels of sidedress nitrogen (N) on agronomic traits of maize cultivated in two regions of Brazilian Cerrado during the summer season. The experiments were conducted during the 2011/12 growing season in Chapadão do Sul and Selvíria Cities, State of Mato Grosso do Sul, Brazil. The experimental design consisted of a randomized complete block design with a 2 × 2 × 5 factorial scheme (with and without inoculation with A. brasilense, two sources of N [regular urea and polymer coated urea], and 5 levels of sidedress N [0, 45, 90, 135, and 180 kg ha-1], with 4 replicates for each location. The inoculation with A. brasilense, in the absence of sidedress N significantly increased the maize yield cultivated in Selvíria. However, the inoculation showed no effect on maize yield when cultivated in Chapadão do Sul. The polymer coated urea provided greater maize yield cultivated in Chapadão do Sul, however, no difference between sources of urea were observed in Selvíria. The greatest levels of sidedress N, without inoculation with A. brasilense showed the greatest maize yield in both locations.